Mesenchymal stem cells derived from adipose tissue accelerate the progression of colon cancer by inducing a MTCAF phenotype via ICAM1/STAT3/AKT axis - Xue, Chunling; Gao, Yang; Sun, Zhao; Li, Xuechun; Zhang, Mingjia; Yang, Ying; Han, Qin; Bai, Chunmei; Zhao, Robert Chunhua (Frontiers in Oncology, 2022)
Previous studies have shown that the risk of colon cancer is greatly increased in obese people, and fat content in colorectal cancer tissue is increased in obese people. As an important part of tumor microenvironment, adipose-derived mesenchymal stem cells(MSCs) are also another important source of cancer-associated fibroblasts(CAFs), which may be one of the important mechanisms of affecting tumor progression. However, the mechanism is poorly defined. In the present study, CAFs were transformed from mesenchymal stem cells (MSCs-transformed CAFs, MTCAFs) by coculturing with HCT116 cells. Bioinformatics and Western blotting analysis indicated a positive correlation between intravascular cell adhesion molecule-1 (ICAM-1) and the progression of colon cancer. In clinical colon cancer specimens, we found that ICAM-1 was high expressed and related to shorter disease-free survival, which might act as an indication for the progression of clinical colon cancer. Our data showed that ICAM-1 secreted from MTCAFs could positively promote the proliferation, migration, and invasion of colon cancer cells by activating STAT3 and AKT signalling, and blocking ICAM-1 in MTCAFs reversed these effects. We further verified that ICAM-1 secreted from MTCAFs promoted tumor progression in vivo. Taken together, ICAM-1 plays a critical role in regulating tumor growth and metastasis, which could be a potential therapeutic target in colon cancer.